Feasibility Analysis for Increasing the Installed Capacity of a Company’s Distribution Center/Warehouse in Cancun - Pérez, Felipe (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4813 The project was conducted at the distribution center/warehouse of Sigma Alimentos Cancún, a frozen-food warehouse and distribution company. The company aimed at determining its actual storage capacity and presenting a proposal to increase its cold storage capacity to meet the demands of the coming years. A four-phase project planning and evaluation methodology was used: market study, technical study, financial and economic study, and results. During the project, these three studies and their results were analyzed. The results of this research suggest to expand the warehouse by increasing its installed capacity to 67,500 kilograms. This expansion will allow the correct operation of the distribution center/warehouse during a minimum of 5 years and even for 9 years.